PENGARUH CSR, UKURAN PERUSAHAAN, LEVERAGE, DAN KEPUTUSAN INVESTASI PADA KINERJA KEUANGAN PERUSAHAAN DAN NILAI PERUSAHAAN - Lais Khafa; Herry Laksitoo (Diponegoro Journal of Accounting, 2015)
This study aims to investigate the influence of Corporate Social Responsibility, firm size,leverage, investment decisions on financial performance, and financial performance on the value of the company.The population in this study is a company listed in Indonesia Stock Exchange in 2012-2013. Sampling was done by purposive sampling. Data analysis with descriptive analysis, the classical assumption test, and multiple regression analysis.Based on the analysis performed, the result that the corporate social reponsibility positiveeffect on firm performance, firm size negatively affect the company's performance, leverage a significant negative effect on the performance of companies, investment decisions positive effect on the company's performance, and the performance of the company a positive effect on firm value.